Implementasi Kurikulum Merdeka Belajar Berwawasan Moderasi Beragama di Sumenep - Abd Warits; Moh Asy'ari Muthhar (Universitas Nurul Jadid, 2024)
The emergence of intolerant understanding is due to the belief that only one's religious understanding is the most correct, while other beliefs are wrong. This phenomenon causes some people to feel